When do we need to consider robotic-assisted radical nephrectomy?—repercussion to the health care cost between 2003 to 2015 - Davila, Hugo H.; Brown, Karisa M.; Storey, Raul E. (Laparoscopic Surgery, 2018)
We would like to congratulate the authors on your research and manuscript, which keeps adding information about the cost of robotic and laparoscopic surgery. We would like to present some suggestions and considerations based on your conclusions. Two questions are important to discuss: (I) why do we need to do a Radical Nephrectomy? (II) Why do we need to use a robotic approach?